Impacts of the baking heating rate on the water mobility, starch microstructure and mechanical properties of degassed crumb during staling. (July 2021) - Bou Orm, Roua; Jury, Vanessa; Falourd, Xavier; Boillereaux, Lionel; Guihard, Luc; LE-Bail, Alain
Abstract: In this study, the impacts of different heating rates (HRs) from 6 to 40 °C/min were investigated in terms of the 1 H proton water mobility, starch microstructure, texture, soluble amylose (AM), amylopectin (AP) retrogradation and AM crystallization during staling. A degassed breadcrumb baked in a miniaturized baking system was used to ensure better time-temperature control during baking. Proton nuclear magnetic resonance ( 1 H NMR) data showed that the evolution of the proton T 2 relaxation time decreased with increasing HR during staling. The amount of soluble AM, AP retrogradation degree, AM crystallization degree and crumb firmness tend to increase at higher HR. Environmental scanning electron microscopy (ESEM) observations showed that most starch granules in crumbs treated at higher HR exhibited strong deformation and disruption. These results confirmed that the increase in crumb firmness during staling with increasing HR was related to a higher level of starch disruption. This yielded a higher degree of separation between the AM and AP, which resulted in more pronounced water trapping in the starch crystals. The resulting dehydration of the matrix (gluten network, with AM gel surrounding of starch granules) yielded a loss in crumb softness, and crumb baked at higher HR tended to have a firmer texture and faster staling. Graphical abstract: Image 1 Highlights: First-order kinetic model confirms that higher heating rate yields faster staling. Starch granules in crumbs treated at higher heating rate exhibits strong deformation. Higher heating rate increases amylose leaching and crystallization during staling. Faster baking increases gluten dehydration and water trapping by starch crystals. Amylose crystallization followed by amylopectin retrogradation yields crumb firming.